Effect of Different Stocking Densities on the Growth and Survival Rate of Tilapia (Oreochromis niloticus) Seeds in Batur Lake Floating Net Cages - Nurazizah, Hikmah; Arthana, I Wayan; Kartika, Gde Raka Anggara (Advances in Tropical Biodiversity and Environmental Sciences; Vol 5 No 2 (2021): ATBESDO - 10.24843/ATBES.2021.v05.i02.p03, 2021)
Stocking density is an important factor in cultivation, it can save land use, and increase the efficiency of fish farming. The purpose of this research was to determine the different density information on tilapia seeds measuring 2-3 cm as an alternative to using tilapia ( O. niloticus ) seeds 7-9 cm in size so that they can be developed in Batur Lake. The research was conducted in January - March 2020 in the floating net cages in Trunyan Kintamani village, Bangli, Bali. The research used a completely randomized design method with three treatments and three repetitions. The Tilapia seeds used are 2-3 cm with different stocking densities, 100 ind/m 3 , 150 ind/m 3 , and 200 ind/m 3 . The parameters observed were SGR ( Specific Growth Rate ), absolute growth, SR ( Survival Rate ), FCR ( Feed Conversion Ratio ), and water quality including temperature, DO, pH, TDS. The results of this study indicated that stocking density did not have a significant effect on the growth and survival rate of tilapia seeds, because the temperature was too cold so that the tilapia seeds failed to adapt properly at the beginning of stocking and the physiological conditions of the fish were disturbed so that the fish experienced stress and went to died. Water quality parameters measured include temperature with a range value of 25.86-25.88 0 C, pH with a range value of 9.08-9.13, DO (Dissolved oxygen) with a range value of 7.9-8 mg/L, and TDS (Dissolved solids) with a range value of 1040.25-1041.58 mg/L.